1973
DOI: 10.1021/jo00948a031
|View full text |Cite
|
Sign up to set email alerts
|

Routes of functionalized guanidines. Synthesis of guanidino diesters

Abstract: Six general methods for the synthesis of acyclic and cyclic guanidines, of structures 1 and 2 and bearing a variety of substituents, are described. These guanidines may be symmetrical or unsymmetrical, and the substituents they bear provide the basis for further chemical manipulation. The acyclic guanidines are derived from single carbon intermediates, such as 3, 9, 13, and 14, and the appropriately substituted amine. The cyclic guanidines result from the functionalization of a 2-p-toluenesulfonamidopyrimidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The preparation of the desired nine-membered ring guanidine 1 follows from oxathiazinane 4 through a series of straightforward functional group transformations (Scheme ). Notable steps in this sequence include the assembly of pseudothiourea 6 using MeS(Cl)CNMbs, a reagent specifically formulated for this work . In addition, sequential reaction of oxathiazinane 6 with Cl 2 CNMbs and (Me 3 Si) 2 NH installs the first of two guanidines while serving to activate the heterocyclic ring for subsequent hydrolytic opening. , Collectively, the conversion of 4 to 8 covers 11 steps and provides a stereodefined acyclic intermediate bearing all of the required components for assembling the tricyclic framework of STX.…”
mentioning
confidence: 99%
“…The preparation of the desired nine-membered ring guanidine 1 follows from oxathiazinane 4 through a series of straightforward functional group transformations (Scheme ). Notable steps in this sequence include the assembly of pseudothiourea 6 using MeS(Cl)CNMbs, a reagent specifically formulated for this work . In addition, sequential reaction of oxathiazinane 6 with Cl 2 CNMbs and (Me 3 Si) 2 NH installs the first of two guanidines while serving to activate the heterocyclic ring for subsequent hydrolytic opening. , Collectively, the conversion of 4 to 8 covers 11 steps and provides a stereodefined acyclic intermediate bearing all of the required components for assembling the tricyclic framework of STX.…”
mentioning
confidence: 99%
“…Surprisingly, only one phosphorylated product could be detected and isolated, and it was identical to the sole product of the creatine kinase-catalyzed phosphorylation of l. 5 The natural abundance, proton-decoupled carbon-13 NMR spectrum of this product was examined. The chemical shift assignments are shown below (relative to dioxane): either 10 or 11 were hydrolyzed, Ar-(2-benzylaminoethyl)glycine dihydrochloride (12) was produced. In analogy to the synthesis of l,5 intermediate 12 was then converted to 7 by treatment with cyanogen bromide in aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of conditions, described elsewhere,9 were used in unsuccessful attempts to phosphorylate 7. Scheme II shows a successful route to the unequivocal synthesis of l-carboxymethyl-2-(diphenoxyphosphinylimino) imidazolidine (13), the diphenyl ester of 3. The scheme was patterned after syntheses of other cyclic guanidines by Bosin et al 12 The use of the powerful methylating agent, methyl fluorosulfonate,13 was found to be necessary for the conversion of 14 to 15. Intermediate 17 was purified by the unusual procedure of chromatography over silica gel of its sodium salt, using methanol as eluent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microwave-assisted synthesis of highly functionalized guanidines on soluble polymer support © 2012 Elsevier Ltd. 51 Synthesis of novel functionalized guanidines and their different reactions have also been extensively carried out by many research groups, employing different approaches. Including the synthesis of dicarbethoxyguanidine, [103] nitroguanidine, [104] nitrotriarylguanidines, [105] N 1 -(6 -Methoxy-8-quinolylaminoalkyl-)guanidines, [106] 1-(Alky1amino)-guanidines, [107] N-alkyl-N'-carboalkoxy guanidines, [108] guanidino diesters, [109] N-guanidino-modified arginines, [110] radioabeled guanidines, [111] pyranosyl nucleosides with guanidine functionality, [112] phosphinyl guanidines, [113] guanidinium chlorides, [114] phase transfer catalyzed alkylation of guanidines, [115] N-triflyl guanidines, [116] cyclic guanidines, [117], [70] monocyclic guanidines, [118] bicyclic guanidines, [25], [119] tricyclic guanidines, [120] tetracyclic guanidines, [121] macrocyclic guanidines, [122] and polycyclic guanidines. [123] …”
Section: Chemical Societymentioning
confidence: 99%